Pengembangan E-Module Pertumbuhan dan Perkembangan Diperkaya Informasi Hubungan Sanitasi Lingkungan dengan Stunting di Desa Jungkat Kabupaten Mempawah - Akbar, Didi; Candramila, Wolly; Mardiyyaningsih, Asriah Nurdini (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
The use of E-Modules in the learning process is useful for increasing learning motivation because the neat packaging can make it easier for students to understand the lesson material. It is also necessary to enrich the module content with important phenomena or cases that can train students' high-level thinking skills. The aim of this research is to develop a teaching material product of an E-Module that addresses the topic of the relationship between stunting and environmental sanitation in Growth and Development material. The development methods used include determining potential and problems, data collection, product design, design validation, and design revision. The module content is divided into three learning activities which are also equipped with summaries, formative tests, evaluation questions, feedback/follow-up, answer keys, and a glossary. The results of content validation by five validators obtained a CVR value = 1 for all indicators from the four aspects, namely graphics, content, presentation, and language. Several revisions according to validator comments/input have been made to improve the quality of the module. The product design is declared valid or suitable to proceed to the next development stage.